ANALISIS KREATIVTAS MAHASISWA DALAM MENYELESAIKAN PEMBUKTIAN LANGSUNG PADA MATA KULIAH TEORI BILANGAN - Prajitno, Sunyoto Hadi (Universitas Pendidikan Mandalika (UNDIKMA), 2020)
The way of thinking logically and reasoning in number theory courses can be seen by the number of proofs of the properties of numbers in some basic set of numbers. This qualitative research aims to analyze student creativity in solving proving questions directly. The research involved 37 third semester students taking lectures on number theory. The technique in this research is to provide a test of proving questions then ask students with their own desires to do in front of the class, analyze the result of students work and interview students about their work. Data analysis was performed by analyzing the creativity of the evidence carried out by students fulfilling which aspects of the aspects of creative thinking behavior and indicators of creative thinking abilities based on Mahmudi. As many as four students have beeb able to use different evidentiary techniques. The four students are creative with very low, low, medium, high creativity ability levels based on fulfillent of indicators of creative thiking abilities based Mahmudi.Â